Novel PAX9 compound heterozygous variants in a Chinese family with non-syndromic oligodontia and genotype-phenotype analysis of PAX9 variants - Jiabao REN; Ya ZHAO; Yunyun YUAN; Jing ZHANG; Yulin DING; Meikang LI; Yilin AN; Wenjing CHEN; Li ZHANG; Boyu LIU; Shushen ZHENG; Wenjing SHEN (University of São Paulo, 2023)
Abstract Studies have reported that >91.9% of non-syndromic tooth agenesis cases are caused by seven pathogenic genes. Objective To report novel heterozygous PAX9 variants in a Chinese family with non-syndromic oligodontia and summarize the reported genotype-phenotype relationship of PAX9 variants. Methodology We recruited 28 patients with non-syndromic oligodontia who were admitted to the Hospital of Stomatology Hebei Medical University (China) from 2018 to 2021. Peripheral blood was collected from the probands and their core family members for whole-exome sequencing (WES) and variants were verified by Sanger sequencing. Bioinformatics tools were used to predict the pathogenicity of the variants. SWISS-MODEL homology modeling was used to analyze the three-dimensional structural changes of variant proteins. We also analyzed the genotype-phenotype relationships of PAX9 variants. Results We identified novel compound heterozygous PAX9 variants (reference sequence NM_001372076.1) in a Chinese family with non-syndromic oligodontia: a new missense variant c.1010C>A (p.T337K) in exon 4 and a new frameshift variant c.330_331insGT (p.D113Afs*9) in exon 2, which was identified as the pathogenic variant in this family. This discovery expands the known variant spectrum of PAX9; then, we summarized the phenotypes of non-syndromic oligodontia with PAX9 variants. Conclusion We found that PAX9 variants commonly lead to loss of the second molars.